Towards a Digital Twin for Open-Frame Underwater Vehicles Using Evolutionary Algorithms - Félix Orjales; Julián Rodríguez-Cortegoso; Enrique Fernández-Pérez; Alejandro Romero; Vicente Diaz-Casas (Applied Sciences, 2025)
Hydrodynamic coefficients determine the behavior of all simulated underwater vehicles. Therefore, it is essential to precisely define their values when aiming to replicate a real vehicle. Generally established procedures for obtaining them tend to have limitations, especially in transient responses. To address these issues, this paper proposes a comprehensive methodology for obtaining the hydrodynamic coefficients of an underwater vehicle. The main novelty is the combination of empirical measurements as a first step and evolutionary algorithms as a final step for optimizing the coefficients. The proposed methodology is described and applied to a commercially available remotely operated vehicle (ROV) BlueROV2, followed by analyzing the results in detail and including several tests that compare it to the real vehicle to validate its adequacy.